Evolutionary history of the Iberian honey bee (Apis mellifera iberiensis): a genome-wide approach - Pinto, M. Alice (2012)
The Iberian Peninsula has been recognized as a hot spot of diversity and endemisms for numerous plant and animal species, and the honeybee is no exception. Honeybees occur naturally in Europe, Africa and the Middle East. In this vast range of habitats, adaptation to the diverse ecological conditions has led to evolution of over 29 subspecies, which have been grouped into five lineages. The Iberian Peninsula harbours two of such lineages (A and M) and the greatest genetic diversity and complexity across Europe. Unraveling the evolutionary forces underlying such complex patterns of diversity has been a major goal of numerous studies and an increasingly important undertaking given the escalating threats to the honeybee populations (e.g. diseases, parasites, pesticides, colony collapse disorder, genetic pollution). Herein we will present an ongoing research project which is using cutting edge molecular and analytical tools to disentangle the evolutionary forces shaping the Iberian honeybee diversity. The genome scan approach used in this study will enable dissection of genome-wide (expansions, contractions, admixture) from genome-specific forces (selection). Furthermore, the honeybee genomic resources will enable exploration of the molecular basis of adaptation. We anticipate that this study will provide unprecedented insights into the history and adaptive divergence of honeybees and the findings can be applied for designing conservation programs of locally adapted ecotypes.